Reply to Troisi et al. Comment on “Cabrera-Aguas, M.; Watson, S.L. Updates in Diagnostic Imaging for Infectious Keratitis: A Review. Diagnostics 2023, 13, 3358” - Maria Cabrera-Aguas; Stephanie L. Watson (Diagnostics)
We appreciate the interest of Troisi and his colleagues [...]